The Role of Religious Coping in Moderating the Relationship between Stress and Non-Suicidal Self-Injury (NSSI) - Elvina, Nadya; Bintari, Dini Rahma (Humaniora: Journal of Indonesia Culture and Society, 2023)
The cross-sectional research aimed to examine the relationship between stress, positive and negative religious coping, and Non-Suicidal Self-Injury (NSSI) severity. It was a global health issue with a high and increasing prevalence among emerging adults. Various factors’ roles in influencing the severity of NSSI had been explored, including stress and religious coping. Data were gathered from 311 emerging adult (age 18-29 years old) participants in Indonesia using an online questionnaire, which included measures of stress (the Perceived Stress Scale-10), positive and negative religious coping (the Brief RCOPE), and NSSI severity (the Non-Suicidal Self-Injury Function Scale). The research reveals that 40,2% of participants have engaged in NSSI. Analysis using simple regression indicates that an increase in stress predicted with statistical significance an increase in NSSI severity. Meanwhile, analysis using moderation demonstrates that negative religious coping has a statistically significant moderation effect on the relationship between stress and NSSI severity. However, moderation analysis indicates that positive religious coping does not have a statistically significant moderation effect on the relationship between stress and NSSI severity. Thus, stress and negative religious coping play important roles in exacerbating NSSI. The research illustrates the importance of prevention and intervention programs for NSSI targeting stress and negative religious coping.